2012
DOI: 10.3797/scipharm.1204-27
|View full text |Cite
|
Sign up to set email alerts
|

Biological Activities of 2-Mercaptobenzothiazole Derivatives: A Review

Abstract: 2-Mercaptobenzothiazoles are an important class of bioactive and industrially important organic compounds. These compounds are reported for their antimicrobial and antifungal activities, and are subsequently highlighted as a potent mechanism-based inhibitor of several enzymes like acyl coenzyme A cholesterol acyltransferase, monoamine oxidase, heat shock protein 90, cathepsin D, and c-Jun N-terminal kinases. These derivatives are also known to possess antitubercular, anti-inflammatory, antitumor, amoebic, anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
50
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(53 citation statements)
references
References 70 publications
(65 reference statements)
0
50
0
3
Order By: Relevance
“…Benzothiazole derivatives present a wide range of biological activities such as, antitumor, antimicrobial, antitubercular, antimalaria, anticonvulsant, anthelmintic, antiinflammatory and analgesic among others, for which, they are of great pharmacological and medicinal interest [1][2][3][4][5][6][7][8]. The incorporation of different groups in the thiazol ring or in both rings improves their pharmacological properties, as reported for the 2-amino-5-(trifluoromethoxy)benzothiazole derivative, named riluzol, which has a NH 2 group in the thiazole ring and a O-CF 3 group in the benzene ring.…”
Section: Introductionmentioning
confidence: 99%
“…Benzothiazole derivatives present a wide range of biological activities such as, antitumor, antimicrobial, antitubercular, antimalaria, anticonvulsant, anthelmintic, antiinflammatory and analgesic among others, for which, they are of great pharmacological and medicinal interest [1][2][3][4][5][6][7][8]. The incorporation of different groups in the thiazol ring or in both rings improves their pharmacological properties, as reported for the 2-amino-5-(trifluoromethoxy)benzothiazole derivative, named riluzol, which has a NH 2 group in the thiazole ring and a O-CF 3 group in the benzene ring.…”
Section: Introductionmentioning
confidence: 99%
“…Molecules with mercaptobenzothiazole (BTA) moiety have different biological activities [4]. Accordingly, 2-Mercaptobenzothiazole (2-MBT) derivatives have a wide variety of applications [5]. 2-MBT consists of Benzothiazole which is a heterocyclic compound, includes benzene ring fused with 4,5 positions of thiazole ring [6,7], and the Mercapto (thiol group) substituent at position 2 of thiazole ring that gives the compound antibacterial and anti-inflammatory activity [8].…”
Section: Introductionmentioning
confidence: 99%
“…In their literature review, Keri et.al. 2 and Azam and Suresh 14 found that the pharmacological activity of these systems has been widely investigated and found efficient.…”
Section: Introductionmentioning
confidence: 99%